Peran Perempuan Dalam Penyelesaian Konflik Dusun Ory Pada Negeri Pelauw dengan Negeri Kariu Kabupaten Maluku Tengah - Tuanaya, Mirza Raisa; Rolobessy, Mike Jurnida; Mahulauw, Syaiful Rijal (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2024)
resolving the conflict berween Ory Hamlet, Pelauw State and Kariu State. This research was carried oud in Ory Hamlet, Pelauw State and Kariu State. Primary data collection techniques were carried out through interviews with a number of informant who were considered to be involved in the process of resolving the conflict between Ory Hamlet, Pelauw State and Kariu State.The results of this research show that so far in conflicts, women and children have only been considered victims, even though the informal effoots made by women have also made a positive contribution to the peacemaking process. However, in formal spaces, women’s involvement I very minimal, because they are not in strategic positions in the leadersip structure.